Acute effects of maximal isometric muscle action of the elbow extensors on contralateral dynamic task of the elbow flexors: a pilot study - Cauê V La Scala Teixeira; Diego R Cortes; Alexandre L Evangelista; Luis T Polito; Danilo S Bocalini; Pablo B. Costa; Roberto Simão; Paulo H Marchetti (Universidade Estadual Paulista (UNESP), 2017)
ABSTRACT Aim the aim was to investigate the influence of a maximal isometric muscle action of the elbow extensors on the contralateral dynamic task of the elbow flexors. Methods Seventeen recreationally trained men (23.3 ± 4.9 yrs, BMI: 24.8 ± 2.2 Kg/m²) underwent two randomized different testing sessions separated by one week. In the control session (CON) all subjects performed a maximum number of repetitions test (RMs) at 75%1RM using the right elbow flexors. The experimental session (EXP) was similar to the CON; however, all subjects were instructed to perform RMs at 75%1RM by using the right elbow flexors and maintaining the maximal voluntary contraction of the left elbow extensors during the test. RMs, rating of perceived exertion (RPE), and training volume (TV) were measured and compared between sessions. Results The EXP showed a significant 10.4% increase on the RMs (13.8 vs. 12.5, p < 0.001, d = 0.44) and 12.1% increase in TV (238.0 vs. 212.4 kg, p < 0.001, d = 0.43) than CON. No differences were observed for RPE between sessions. Conclusion The maximum voluntary contraction of the left elbow extensors increased the RMs of the contralateral elbow flexors, reflecting a higher TV, and no differences in the RPE. Our results suggest that the investigated method may be a viable and practical alternative to increase the acute strength performance of elbow flexors when using submaximal loads.